2015
DOI: 10.1007/s12076-015-0144-4
|View full text |Cite
|
Sign up to set email alerts
|

On real estate development activity: the relationship between commercial and residential real estate markets

Abstract: Real estate development and the construction of commercial and residential buildings largely determine the future spatial distribution of job and residential locations, thereby giving public planners an instrument with which they can steer urbanization. This paper measures whether the real estate development and urban management planning process, in terms of construction permits, enables a relationship between commercial and residential real estate developments and thus between future job and residential locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Additionally, a general description of variables of the building construction process, as significantly impacting the parameters of the whole economy, and in particular -the real property market -can be found, among others in the works of Mach and Racka (2018), Geipele and Auzins (2015) and Mach (2016). On the other hand, we can find descriptions of making use of the factor in the form of issued building permits and its impact on the conditions of the real estate market in the works by Mach (2012), Go (2013), Somerville (2001) and Schoenmaker and Vlist (2015). Also, an analysis of prices and their indexes appears vital from the point of view of research into the real estate market (cf.…”
Section: Research Assumptions and Research Methodologymentioning
confidence: 95%
“…Additionally, a general description of variables of the building construction process, as significantly impacting the parameters of the whole economy, and in particular -the real property market -can be found, among others in the works of Mach and Racka (2018), Geipele and Auzins (2015) and Mach (2016). On the other hand, we can find descriptions of making use of the factor in the form of issued building permits and its impact on the conditions of the real estate market in the works by Mach (2012), Go (2013), Somerville (2001) and Schoenmaker and Vlist (2015). Also, an analysis of prices and their indexes appears vital from the point of view of research into the real estate market (cf.…”
Section: Research Assumptions and Research Methodologymentioning
confidence: 95%
“…Several studies have shown that the number of building permits that developers obtain is a critical factor in the future performance of their business [25][26][27]. Obtaining building permits indicates full readiness to start new construction projects, and the number of construction projects actually started is an indicator of the developer's commitment to new investments.…”
Section: Changes In Housing Market In Poland During the Covid-19 Pand...mentioning
confidence: 99%
“…Multiple works of literature obtained were found to define real estate development from an individual or standalone (microeconomic) basis only, regarding it as a "process of land development to construct commercial and residential buildings" (Schoenmaker & Van der Vlist, 2015).…”
Section: Definition Of Real Estate Developmentmentioning
confidence: 99%